Hubungan Usia dan Paritas Ibu dengan Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Upt Puskesmas Sei Panas Kota Batam Tahun 2024 - Tengku Yunita Febrianti; Resi Novita; Anisya Selvia (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Problems: Based on data from the Batam City Health Office, the 3 Community Health Centers with the highest incidence of anemia include Sei Panas 15.7%, Sambau 10.24%, Nongsa 8.24%. Objective: This study aims to determine the relationship between maternal age and parity with the incidence of anemia in pregnant women in the working area of UPT Puskesmas Sei Panas Batam City in 2024. Methods: This study used a descriptive correlation research design with a cross-sectional research design. The sampling technique used was Non Probability Sampling. Respondents in this study were 66 pregnant women. Results: Based on the Chi- Square test, the age variable obtained a P-value of 0.000 (ρ <0.05) and the parias variable with a P-value of 0.000 (ρ>0.05). This study shows that there is a relationship between age and the incidence of anemia in pregnant women and the relationship between parity and the incidence of anemia in pregnant women in the working area of UPT Puskesmas Sei Panas Batam City in 2024. Conclusion: there is a relationship between age and parity of mothers with the incidence of anemia in pregnant women. Suggestion: It is hoped that prospective mothers understand the ideal safe age and parity in preparing for a healthy pregnancy in order to avoid anemia during pregnancy. And pregnant women must be diligent in consuming Fe tablets and also make 6 ANC visits during pregnancy so that pregnant women's health is monitored, especially their Hb levels.